Persepsi Penerapan Wajib Militer Guna Meningkatkan Pendidikan Bela Negara - Utari Maharani Noor (Universitas Widya Gama Malang, 2020)
In the constitution of Republic Indonesia 1945 regulate that all Indonesian citizens should participate to defend the country. It occur in subsection of 27 verse 3 said, “All Indonesian citizens have a right and should participate to defend the country.” The development of defend the country action can be do with some way such as giving a conscription education a though some country who obligate the citizens especially men to do conscription like in South Korea. The basic military training in Indonesia only given to National Indonesian Military who their essence is a thing that directly related with them occupation they do. This journal will explain how the society perception if the application of conscription applied and how the form of the basic military training that appropriate for the student, collage students also people who wants to jump in the world of work.